Racial/ethnic disparities in the association of maternal diabetes and obesity with risk of preterm birth among 17 million mother-infant pairs in the United States: a population-based cohort study - Xie, Juan; Yan, Yuxiang; Ye, Ziyi; Wu, Yuxiao; Yu, Yongfu; Sun, Yangbo; Rong, Shuang; Santillan, Donna A.; Ryckman, Kelli; Snetselaar, Linda G.; Liu, Buyun; Bao, Wei (BMC pregnancy and childbirth, 2025)
Background The racial/ethnic disparities in the prevalence of obesity, diabetes, and adverse birth outcomes such as preterm delivery indicate that it is essential to account for the varying risks associated with pregnant women of different races and ethnics during clinical prenatal examinations. However, the racial and ethnic disparities in how pre-pregnancy diabetes in mothers relates to preterm birth as well as the combined association of maternal diabetes and pre-pregnancy obesity with preterm birth remain unclear. In this study, we aimed to 1) examine the racial/ethnic disparities in the association of maternal diabetes including gestational diabetes mellitus (GDM) and pre-pregnancy diabetes with preterm birth 2) and the racial/ethnic disparities in the joint associations of maternal diabetes and pre-pregnancy obesity with preterm birth. Methods In this population-based cohort study, we included 17,027,792 mothers documented in the National Vital Statistic System in the U.S. from 2016 to 2020. All these data were analyzed in 2021. Maternal pre-pregnancy diabetes was defined as having diabetes diagnosed prior to this pregnancy, and GDM was defined as having newly diagnosed diabetes in this pregnancy. Pre-pregnancy BMI (kg/m 2 ) was classified as underweight (< 18.5 kg/ m 2 ), normal weight (18.5–24.9 kg/m 2 ), overweight (25.0–29.9 kg/m 2 ), obesity class I (30.0–34.9 kg/m 2 ), obesity class II (35.0–39.9 kg/m 2 ), and obesity class III (≥ 40 kg/m 2 ). Preterm birth, defined as delivery occurring at less than 37 weeks of gestation, was the main outcome of interest. We further categorized preterm birth into three subtypes: extremely (< 28 weeks), very (28–31 weeks), and moderately (32–36 weeks) preterm birth. Logistic regression models were used for association analyses in this study. Results Among 17,027,792 mothers (mean age: 29.4 ± 5.4 years), 1,374,286 (8.07%) mothers delivered a preterm infant. Women with pre-pregnancy diabetes had the highest risk of preterm birth followed by women with GDM overall and across all racial/ ethnic groups. However, from pre-pregnancy underweight to obesity III, the magnitude of the association between pre-pregnancy diabetes and preterm birth decreased for non-Hispanic Black women (underweight, 4.47 [3.34–5.99], normal weight 4.28 [3.98–4.60], overweight 3.29 [3.11–3.49], obesity I 3.09 [2.93–3.26], obesity II 2.98 [2.82–3.16], obesity III 3.19 [3.04–3.35]), while it showed an increasing trend for non-Hispanic Asians ( underweight 1.45 [0.91–2.30], normal weight 2.16 [1.90–2.47], overweight 2.71 [2.47–2.97], obesity I 3.10 [2.82–3.41], obesity II 3.58 [3.13–4.09], obesity III 3.99 [3.34–4.77]). The corresponding OR was (underweight 4.33 [3.21–5.83], normal weight 3.69 [3.47–3.93], overweight 3.26 [3.10–3.42], obesity I 3.33 [3.19–3.49], obesity II 3.47 [3.29–3.65], obesity III 3.89 [3.68–4.11]) among Hispanics and (underweight 5.17 [4.34–6.17], normal weight 5.01 [4.83–5.21], overweight 4.98 [4.80–5.17], obesity I 4.66 [4.48–4.85], obesity II 4.58 [4.38–4.79], obesity III 4.50 [4.31–4.69]) among non-Hispanic White. Comprehensive analysis of the association between diabetes, pre-pregnancy diabetes, obesity, ethnicity, and preterm birth found that compared to white women with normal weight and normal blood glucose levels, any other racial\ethnic group has an elevated risk of preterm birth, particularly when accompanied by unhealthy weight, GDM, or pre-pregnancy diabetes. Specifically, non-Hispanic Black individuals with normal blood sugar levels (1.69 [1.67–1.70]) have a higher risk of preterm birth than non-Hispanic White individuals with GDM (1.37 [1.35–1.40]). Similarly, Asian pregnant women with class 2 and class 3 obesity (1.72 [1.65–1.78], 1.96 [1.83–2.10]), as well as Hispanic pregnant women with class 2 and class 3 obesity (1.46 [1.44–1.48], 1.64 [1.61–1.67]), also have a higher risk of preterm birth than white women with GDM 1.37 [1.35–1.40]. Conclusions In conclusion, while both pre-pregnancy diabetes and GDM were significantly associated with preterm birth, the associations varied by race/ethnicity. The risk of preterm birth for GDM increased with increasing BMI in all race/ethnicity groups. However, the pattern of the joint association of pre-pregnancy diabetes and BMI levels with preterm birth differed by race/ethnicity. Future studies on the underlying mechanisms of the racial/ethnic disparities in the association of diabetes and obesity with preterm birth are needed.